Perlindungan Hukum atas Kekerasan Seksual bagi Remaja Perempuan di Indonesia - Salsabila, Nabila Wista; Suherman, Asep (Verdict: Journal of Law Science, 2022)
Legal protection for women from acts of sexual violence and freedom from torture or treatment that degrades human dignity is the right of all citizens which is a constitutional right guaranteed in the 1945 Constitution. Sexual violence in Indonesia occurs in various circles. Starting from children, teenagers, to adults. In fact, it doesn’t only happen to women, but also to men. Not only various groups, sexual violence can also occur anywhere, namely the workplace, public places, places of study and even in the family environment. This type of research is normative legal research, namely legal research carried out by examining library materials or secondary date. The form of law enforcement provided by the Criminal Code for Sexual Violence against minors is criminal responsibility for the perpetrator and focuses on personal responsibility rather than direct and specific responsibility for the victim’s loss/pain. Law enforcement against perpetrators of criminal acts of sexual violence is confirmed in Law Number 35 of 2014 concerning Child Protection and Law Number 12 of 2022 concerning Crimes of Sexual Violence. Special protection for child victims of sexual crimes is carried out through: education about reproductive health, religious values ​​and moral values; social rehabilitation; psychosocial assistance during treatment until recovery; and providing protection and assistance at every level of examination starting from investigation, prosecution to examination in court.